CREATION OF THE DANCE MUSIC FOR THE PUCUK BANG MASCOT OF BANGLI REGENCY - Garwa, I Ketut (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Pucuk Bang, or Hibiscus Rosa-Sinensis, was established as the identity and mascot of Bangli Regency during the leadership of Regent I.B. Gede Agung Ladip (1990–1995, 1995–2000) and officially declared on Bangli's 771st anniversary on May 10, 1991. Regent Sang Nyoman Sedana Arta (2021–2026) aimed to revive Bangli's taksu through the creation of the Pucuk Bang Dance as a visual icon, communication medium, identity symbol, and representation of Bangli’s vision and mission, fostering emotional connections and broad acceptance. The Pucuk Bang flower embodies purity, love, sincerity, and courage.